Increasing of Spectral Resolution of Multislit Imaging Spectrometer with Diffractive Grating - I. M. Gulis; A. G. Kupreyeu (Приборы и методы измерений)
Registration of non-stationary processes, namely snapshot hyperspectral imaging that allows to capture data cube I(x,y,λ) in one measurement act, is of interest for imaging spectroscopy.The purpose of the work is increasing of spectral resolution of imaging spectrometers with spatial filtering of object image using multislit mask, where a diffractive grating is used as disperser (providing almost constant dispersion in working spectral range), and the data cube is projected on a detector as a set of local spectra from object fragments.An image is formed on detector by a two-objective telecentric system composed from two lenses focused on infinity so that their front focuses are matched. A diaphragm in the match point allows passing only for beams of needed diffraction order, so along with a bandpass filter near the system entrance they solve a typical problem of diffractive systems – elimination of beams of all orders but a needed one. The approach is implemented in two proposed designs of spectrometers: in the first a telecentric system is based on two multi-lens imaging objectives, in the second – is based on two reflective off-axis parabolic objectives.In this paper we proposed variants for optical design optimization: normalization of beam incidence on a mask and field curvature compensation; they allow to increase system resolution and to extend application area of multislit dispersive spectrometers; also a design being a synthesis of these two approaches is analyzed. According to simulation results, width on half-maximum in dispersion direction Δl ≤ 10 µm, only for limited field points set Δl ≤ 15 µm, that stands for spectral resolutio